(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Recently, the idea of reconfigurable antennas has made it feasible to design a single antenna that can support multiple wireless standards while maintaining the same performance as multiple antennas. The integration of a single antenna that can operate at multiple frequencies is required to enable multiple applications in a single device. This paper presents a compact frequency-reconfigurable microstrip antenna designed to support multiple wireless standards in modern communication devices. The proposed antenna, with dimensions of 30 × 15 × 1.52 mm³, is simulated using CST Studio Suite and achieves reconfigurability through the integration of PIN diodes as switches within strategically placed slots on the radiating structure. By controlling the bias states of the two PIN diodes (Sw1 and Sw2), the antenna can dynamically switch between four distinct operating modes: All switches ON: dual-band operation at 2.4 GHz (lower WLAN) and 5.6 GHz (higher WLAN), All switches OFF: single-band resonance at 4.2 GHz (radio altimeter applications), Sw1 ON and Sw2 OFF: single-band operation at 2.9 GHz (military and meteorological radars), Sw1 OFF and Sw2 ON: dual-band coverage at 3.5 GHz (5G sub-6 GHz) and 5.6 GHz (higher WLAN/5G). The design maintains consistent performance across these configurations while offering a low-profile, single-antenna solution that eliminates the need for multiple dedicated radiators. This makes it highly suitable for integration into space-constrained devices such as smartphones, laptops, tablets, IoT systems, and next-generation wireless networks. The proposed antenna demonstrates versatile multiband/frequency agility compatible with WLAN, 5G, radio altimeters, military radars, and weather radar applications, highlighting its potential to address the growing demand for efficient, multifunctional antennas in emerging wireless ecosystems.